Neem oil as biopesticides - Izahudin, Muhammad Haziq; Rosmi, Muhammad Hilman; Mohd Fauzi, Noor Akhmazillah (Penerbit UTHM, 2022)
Agricultural biotechnology is a wide logical method used to improve plants, animals, and microorganisms. The biotechnology cycle in the agricultural segment incorporates improving the harvests, living things, and microorganism's quality and resistibility by hereditary adjustment. Other than that, biotechnology in agriculture additionally known from the utilization of more secure natural sources to create an item that will be ready to ensure and build the creation of yields and domesticated animals, for example, manure and biopesticides. The World Health Organization (WHO) likewise had reported that the synthetic based pesticides would arrive at their constraints of utilization as it loses their adequacy after some time. This can be shown by the disclosure of pesticides obstruction bugs. The neem plant was accounted for as the top rundown spices that can possibly go about as a biopesticide; this is because of the presence of various dynamic mixes known as limonoids. The significant compound is the azadirachtin which assumes an essential job as bug sprays, and it executes the focused-on bugs by troubling their development and generative system. The neem oil biopesticides additionally are less harmful towards living beings and less contamination toward nature. In this way, the neem removed biopesticides are presently popularized and have been sold and utilized in different nations.